2018
DOI: 10.1055/s-0043-122672
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Follow-up of Canaliculotomies after Canaliculitis

Abstract: The canaliculi remained open within the long-term follow-up period without any drawbacks to the lacrimal outflow. No recurrent infections were seen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 16 publications
(41 reference statements)
0
7
0
2
Order By: Relevance
“…Canaliculotomy allows better access to the canaliculus and more thorough curettage of canalicular contents. Canalicular curettage after canaliculotomy carries a high remission rate and is one of the options for primary canaliculitis [7,9,10,12,30]. However, in patients with canalicular dilatation, canaliculotomy alone may not be sufficient because it fails to reconstruct the anatomical structure of canaliculus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Canaliculotomy allows better access to the canaliculus and more thorough curettage of canalicular contents. Canalicular curettage after canaliculotomy carries a high remission rate and is one of the options for primary canaliculitis [7,9,10,12,30]. However, in patients with canalicular dilatation, canaliculotomy alone may not be sufficient because it fails to reconstruct the anatomical structure of canaliculus.…”
Section: Discussionmentioning
confidence: 99%
“…The surgical procedures are well known in the literature [9][10][11]. In brief, following local anesthesia, a canaliculotomy incision was made through conjunctival approach parallel to the dilated horizontal canaliculus, and curettage was performed to evacuate concretions inside the canaliculus.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Canaliculotomy and punctoplasty enable better removal of canalicular content and generally heal without complications. 2,7,13,18 However, complications such as narrowing of the canaliculus, lacrimal pump dysfunction, and lacrimal fistulae may occur in rare cases and lead to epiphora in the long term. Kim et al 19 reported epiphora in 8.7% of the patients they treated with three-snip punctoplasty and curettage and followed for a mean of 11 months.…”
Section: Discussionmentioning
confidence: 99%
“…A. Salam и соавторы также описали случай, когда проходимость слезоотводящих путей была восстановлена после удаления конкремента через естественные пути [7]. Существуют и другие подобные сообщения, поддерживающие нашу гипотезу; к тому же широко известно, что кюретаж полости слезных канальцев при каналикулите является высокоэффективным вмешательством, а рецидивы после него редки [8][9][10]. В настоящее время уже разработаны консервативные способы лечения пациентов с мочекаменной болезнью, которые показали свою высокую эффективность, однако разработка таких методик потребовала наличия мощной фундаментальной и клинической научной базы, включая генетические, химико-аналитические и физико-механические исследования [11].…”
Section: обзоры литературы Literature Reviewsunclassified